The economic determinants of tourism seasonality: A case study of the Norwegian tourism industry - Jinghua Xie (Cogent Business & Management, 2020)
Since seasonality has long been recognized as one of the most critical problems in the tourism industry, many studies have been conducted to investigate its reasons. Nevertheless, almost all the studies focus on climate and institutional reasons, ignoring the possible economic determinants. In this study, we use econometric models to estimate how economic factors such as tourist's income, the relative costs in a tourist's home country, and destination country affect tourism seasonality, using the seasonal demand of the Japanese and Chinese tourists in the destination of Norway as a case study. The results suggest the long-ignored economic determinants are crucial in affecting tourism seasonal concentration. Various price strategies by considering the different price sensitivity of tourists in peak and off-peak seasons are necessary to modify seasonality. The mitigating effect of economic growth on tourism seasonality is parallel to the level of economic development. The finding is in line with the expectation that global tourism seasonality due to tourists from emerging markets may debilitate as these countries keep up with growth in the future.
Keywords: 650; economic determinant; income; relative price; tourism seasonality; Norway